Associations between family factors and body weight gain from 20 years old - Wakako Suzuki; Wuren; Kiyonori Kuriki; Shizuoka-Sakurag (BMC, 2019)
Abstract Background Although family factors can greatly impact adult health, little is known about the extent to which family factors are related to body weight gain (BWG) in adulthood. This study aimed to examine the associations between family factors and BWG from 20 years old. Methods Among the 6395 possible participants aged 35 to 79 years, 2884 men and 2171 women were eligible for the study. Present body mass indexes (BMI) were measured, and family factors and body weight from 20 years old (i.e., BMI_20yr) were collected using a self-administered questionnaire. The differences between BMI and BMI_20yr were calculated, and those with increases of BMI ≥2.5 kg/m2 (i.e., ≥7.5 and 6.0 kg in men and women, respectively) were defined as 'cases' of BWG. Using a multiple logistic regression analysis, the odds ratios (ORs, 95% confidence intervals [CIs] and p for trend) were estimated. Results In the men, no association was found. In the women, the ORs were 0.31, 1.00 and 0.77 (0.17-0.58, [reference], and (0.52-1.29), p < 0.001) as per their marital status: unmarried, married, and bereaved/divorced, respectively. Although no association was found with family structure (i.e., single, couple, and two and three generations living together), for familial relationships, the ORs were 1.00, 1.11 and 1.86 ([reference], 0.85-1.46, and 1.25-2.79, p < 0.01) for 'good', 'somewhat good', and 'not so good/not good', respectively. Even if a 'case' of BWG was ≥3.5 kg/m2, nearly the same risks remained. Conclusion Marital status and family relationships were associated with decreased and increased risks of BWG only in the female participants. Family factors should be considered when advising women on body weight control.